2015
DOI: 10.1111/jfbc.12144
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Visual Changes in Cactus Stems (Opuntia ficus-indica Mill.) Stored at 4, 12 and 26C

Abstract: The purpose of this study was to identify visible and microscopic symptoms as well as certain biochemical changes associated with chilling injury (CI) in "Atlixco" cactus stems. Cladodes were harvested, disinfected, minimally processed and stored at 4, 12 and 26C for 14-21 days. Results indicated that cactus stems were sensitive to CI at 4 and 12C and exhibited pitting and bronzing as visible symptoms of this disorder. Confocal microscopy showed that mitochondrial integrity was maintained at 4C whereas a deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In relation to the postharvest life of minimally processed cactus stems stored under different temperatures, Rodríguez‐Verástegui et al . studied their cellular structure and the damage caused to the epidermis.…”
Section: Chemical Composition Changes Of Cactus Stemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the postharvest life of minimally processed cactus stems stored under different temperatures, Rodríguez‐Verástegui et al . studied their cellular structure and the damage caused to the epidermis.…”
Section: Chemical Composition Changes Of Cactus Stemsmentioning
confidence: 99%
“…Thus, it is recommended to consume younger cactus stems in order to help regulate blood sugar levels and accelerate nutrient absorption in the gut. 49 In relation to the postharvest life of minimally processed cactus stems stored under different temperatures, Rodríguez-Verástegui et al 50 studied their cellular structure and the damage caused to the epidermis. They reported that the cactus stems without thorns and stored at 26 ∘ C, presented a break-up in the cellular structure and water loss after 7 days, resulting in a product with a fibrous texture associated with water loss.…”
Section: Total Dietary Fibermentioning
confidence: 99%
“…Additionally, as was previously discussed, the use of a CO 2 ‐rich atmosphere also enabled the preservation of most of the original green color in Atlixco stems, particularly when compared with the other two atmospheres analyzed (i.e., 100% N 2 and air). In this sense, past studies have concluded that CO 2 does significantly delay the senescence of chloroplasts (at least in banana peels, Song et al, ), and it is quite telling that such organelles are particularly abundant in the chlorenchymal tissues of cactus stems (Rodríguez‐Verástegui et al, ). These two explanations could therefore be the reasons behind the results obtained with the 10% CO 2 + 90% N 2 atmosphere.…”
Section: Results and Discusionmentioning
confidence: 96%
“…A 400 μl sample of this elute was additionally mixed with 100 μl of dithiothreitol (DTT, Sigma‐Aldrich) at 5% (w/v), kept in the dark overnight at room temperature, and used to quantify DHA. Analysis of both compounds was performed on an Agilent 1260 Infinity HPLC (Santa Clara, CA) according to the conditions of operation described by Rodríguez‐Verástegui et al (). Measurements were made at 254 nm (Nour, Trandafir, & Ionica, ) using a variable multiple wavelength detector (VMWD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation